A Comparative Study on Conventional Bitumen Concrete Mix and Ethylene Vinyl Acetate Modified Bitumen Concrete Mix (International Journal of Innovative Research in Engineering & Management, 2023)
Bitumen is often used in the building of  flexible pavements in the capacity of a binder. In the  current investigation, it is suggested that the characteristics  of bitumen might be improved by modifying it with EVA  polymer. The useful life of pavements may be shortened as  a consequence of rutting. In the event that the rutting depth  is very severe, water may pool in the pavement area, which  may cause vehicles to hydroplane. The results of a bending beam rheometer test (BBR) for  creep stiffness at lower temperatures indicate that the creep  stiffness of modified bitumen was lowered, while the m value was enhanced. The in-situ polymer modified binders  that were produced demonstrated significantly reduced  stiffness and satisfied the required parameters up to a  temperature of -18 degrees Celsius.
Keywords: Bitumen; Paving Bitumen; Bitumen Concrete Mix; Ethylene Vinyl Acetate